ANTI-INFERTILITY EFFECTS TEST OF DATE PALM FRUIT EXTRACT (PHOENIX DACTYLIFERA L.) IN FEMALE MICE (MUS MUSCULUS) COMPARED WITH PROPOLIS - Dillasamola, Dwisari; A, Almahdy; Anggraini, Ria; Diliarosta, Skunda; Oktomalio P, Biomechy; Noverial, Noverial (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The date palm (Phoenix dactylifera L) is one of the plants empirically used to increase fertility. The aim of this study was to compare the effect of ethanol extract of date palm fruit and propolis on fertility in female mice. Methods: 5 groups were assigned to 1 control and 4 experimental groups. The experimental group treated by oral administration of 100, 200 and 400 mg/kgBW of khalal date fruit extract and 200 mg/kgBW of propolis for 5, 10 and 15 days. Control groups received no extract. After 5, 10 and 15 days the mice were deeply anesthetized with anesthetic ether and sacrificed. Histological changes in ovary and uterine were measured. The data was analyzed by using two way ANOVA and Duncan test. Results: The results of the study of the effect of the dose and duration of the ethanol extract of khalal date fruit on the histology of ovaries and uterine mice showed that there was an increase in the number of primary, secondary, tertiary, degraaf, and corpus luteum follicles but did not affect the follicle of atresia and myometrial and endometrial thickness. in Propolis a dose of 100mg / kgBW increase occurs only in primary, secondary and corpus luteum follicles. Conclusion: Ethanol extract of khalal date fruit and Propolis can increase the number of ovarian follicles. Ethanol extract of khalal date fruit dose can increase the number of ovarian follicles higher than propolis.